PENGARUH FAKTOR MAKRO EKONOMI TERHADAP INDEKS HARGA SAHAM GABUNGAN (STUDI KASUS DI BURSA EFEK INDONESIA PERIODE JANUARI 2020 HINGGA DESEMBER 2023) - Asmarita, Sri; Mirra Sriwahyuni; Yudi Partama Putra (Universitas Muhammadiyah Bengkulu, 2025)
The aim of this research is to determine how macroeconomic factors affect the composite stock price index (case study on the Indonesia Stock Exchange for the period Januari 2020 to Desember 20203). The background of this research focuses on the composite stock price index on the Indonesia Stock Exchange. The data analysis technique used is multiple linear regression with SPSS 22. The results of the study show that based on the t-test result for the inflation variable, the significance is 0.739, which means greater than 0.05. Thus, it can be concluded that the inflation variable does not affect the IHSG. For the t-test result of the interest rate variable, the significance value is 0.340, which means it is greater than 0.05. It can be concluded that the interest rate variable does not significantly affect on the IHSG. For the t-test results of the exchange rate variable, the significance is 0.000, it can be concluded that the exchange rate variable significantly affects the IHSG. Keywords: Composite Stock Price Index, Inflation, Interest Rate, Exchange Rate